The Essence and Content of Product Distribution as an Economic Category - Viktoriia Bozhkova; Mykhailo Bilukha (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The volatile and turbulent environment requires the ability to timely identify, analyze and counteract challenges in the field of product distribution, which is the key to sustainability, competitiveness and successful development of business entities. Effective distribution not only optimizes distribution processes but also enhances the efficiency of management decisions, which helps to reduce costs and increase profitability. At the same time, the lack of clear conceptual approaches to defining the essence of distribution complicates the integration of its various aspects into a unified management system and requires a comprehensive understanding of the theoretical foundations for the study of distribution as an economic category. In order to systematize the existing approaches to the concept of “product distribution”, a content analysis of definitions presented in the works of scholars was conducted; based on the structural and logical analysis, the key components of the content of this concept were allocated; using the methods of comparison and analogy, common and distinctive features in the interpretation of the essence of distribution by different researchers were identified; taking into account a thorough analysis of the advantages and disadvantages of existing approaches to the definition of product distribution, the author's vision was substantiated using the methods of induction and deduction. Thus, the study made it possible to systematize current approaches to defining distribution in terms of chronology and three-component structure (essence, content and result of the phenomenon), which served as the basis for the author's definition. The authors propose to understand distribution as a complex system that ensures timely and efficient movement and sale of necessary products to end consumers in accordance with their needs and demands with a high level of service and realization of economic interests of participants. Therefore, the proposed definition of the concept of “distribution” combines the key aspects of the definitions presented in the literature, conceptually reflects its essence and content with an emphasis on a systematic approach and covers marketing, logistics and commercial contexts.